A preliminary study of phosphodiesterases and adenylyl cyclase signaling pathway on red blood cell deformability of sickle cell patients - Goksel, Evrim; Ugurel, Elif; Nader, Elie; Boisson, Camille; Muniansi, Ingrid; Joly, Philippe; Renoux, Celine; Gauthier, Alexandra; Connes, Philippe; Yalcin, Ozlem (Frontiers in Physiology, 2023)
This is a provisional file, not the final typeset article deformability before and after the shear stress application. Non-selective PDE inhibition with Pentoxifylline increased RBC deformability. However, modulation of the different PDE types had distinct effects on RBC deformability, with PDE1 inhibition by Vinpocetine increasing deformability while PDE4 inhibition by Rolipram decreased RBC deformability after the shear stress application. The effects of the drugs varied greatly between patients suggesting some could benefit from one drug while others not. Developing drugs targeting the AC signaling pathway could have clinical applications for SCD, but more researches with larger patient cohorts are needed to identify the differences in the responses of sickle RBCs.